Text of telegram - Schevenels, Walther, b. 1894
1936-08 Situation Espagne 59 ANGLETERRE CITRINE TRADUNIC SOWEST LONDRES AFTER FRESH CONSULTATION SPANISH COMRADES AGREE AMBULANCE UNIT BE SENT FROM ENGLAND STOP ALSO ALREADY WIRED DUBINSKY APPROVAL FORMATION COMMITTEE RAISE AMERICAN FUNDS FOR SPAIN STOP LETTER FOLLOWS SCHEVENELS Fédération syndicale internationale, 9 ave. d'Orsay, Paris 7e. 292/946/10/140